A Comprehensive Review on the Therapeutic Potential of Chromolaena Odorata for the Management of Foot Ulceration and Chronic Wounds - Mohamed Ali Seyed,; Mahmoud Elodemi,; Adel Ibrahim alalawy, (Pakistan Journal of Medical & Health Sciences, 2024)
The practice of plant derived traditional medicines are considered as one of the excellent tools to enhance the wound healing by reducing healing time and financial burden to the affected ones. In recent years, attention on wound healing medicinal herbs have tremendously improved with the incorporation of multidisciplinary systematic exploratory approach. It is known that many bioactive principles are participated in the healing process with the participation of radical scavenging and anti-pathogenic activities. Though numerous pharmaceutical formulations and preparations are in place and employed for wound repair management, yet the search continues for efficient options, as certain existing therapeutic formulations produce undesirable effects or absence of effectiveness. Phytochemical metabolites from various medicinal plants exhibited abundant ability on various stages of the wound healing shown by numerous molecular mechanisms, thus they are designated as prospective drugs or drug leads of traditional medicine source. Chromolaena odorata (CO) (L.) R.M. King and H. Robinson is recognised as a neglected temperate weed plant. It demonstrated different medicinal properties, which include cytotoxic and other significant actions against pyretic, inflammation, microbes, and analgesic. Besides, in many parts of world it is used for various ailments. To understand its precise role in wound healing and its impact on reasonable health management, this herb requires scientific evaluation based on the existing reports, which are vital for drug design and development. In conclusion, the current review signifies the importance of CO derived phytocompounds for their wound healing potential especially on foot ulceration and chronic wounds. This review highlights the importance and clinical significance of CO which may be benefit the drug screening and pharmaceutical advancement in the field of human and animal medicine. Keywords: C. odorata, CO, foot ulceration, chronic wounds, wound healing, medicinal herbs